Definition of an equivalent functional unit for structural concrete incorporating recycled aggregates. (1st September 2016) - Dobbelaere, G.; de Brito, J.; Evangelista, L.
Highlights: Definition of an equivalent functional unit for Life-Cycle Assessment (LCA) analyses. Concrete with recycled aggregates (RA) versus conventional structural concrete. Equivalent properties of RAC in function of the same property in RC are used. The methodology was validated in 100% of the slabs and 95% of the beams tested. Abstract: This research intends to determine an equivalent functional unit in concrete with recycled aggregates (RA) to conventional structural concrete in the context of Life-Cycle Assessment (LCA) analyses. The work intends to contribute to a better understanding and greater confidence in the use of concrete products with RA. The relationship between recycled aggregates concrete (RAC) and conventional concrete (RC) is expressed by fundamental parameters α, which describe the relevant equivalent properties of RAC in function of the same property of RC. Using those parameters, the study performs a thorough analysis according to Eurocode 2 (EC2): the various compliance checks with the limit states are performed in order to obtain the amount of recycled aggregates concrete required to reach the same performance as a given volume of conventional structural concrete. Conversion criteria for concrete structures with RA (concerning its structural performance) are established and the conversion formulas are tested in case studies. This study is developed particularly for slabs and beams, but remarks are made concerning other main structural elements, namely columns and footings. The results show that the method is valid for slabs and beams and that the conversion formulas yield good results.